The Influence of model fidelity and uncertainties in the conceptual design of Arctic maritime transport systems. Issue 1 (2nd January 2017) - Bergström, Martin; Erikstad, Stein Ove; Ehlers, Sören
ABSTRACT: This paper helps the designer of an arctic maritime transport system (AMTS) to determine an appropriate level of model fidelity with regards to the estimation of transport capacity and ice loading, as well as to understand and manage related design uncertainties. The study is centred around two case studies: 1. The design of an AMTS for independent operation along an arctic route, 2. The design of an AMTS for icebreaker assisted operation along a Baltic route. The outcome of the study indicate that the required model fidelity and the related model uncertainties are case specific. In comparison with the Baltic case, the arctic case required a higher level of model fidelity, and demonstrated a higher sensitivity to uncertainties. In both cases, it proved feasible to mitigate uncertainty with regards to the estimated transport capacity either by increasing the payload capacity of the fleet, or by increasing ship speed.